Measuring mental health burden in humanitarian settings: a critical review of assessment tools - Ashley Moore; Joris Adriaan Frank van Loenhout; Maria Moitinho de Almeida; Pierre Smith; Debarati Guha-Sapir (Taylor & Francis Group, 2020)
Background The effects of disasters and conflicts are widespread and heavily studied. While attention to disasters' impacts on mental health is growing, mental health effects are not well understood due to inconsistencies in measurement. Objective The purpose of this study is to review mental health assessment tools and their use in populations affected by disasters and conflicts. Method Tools that assess posttraumatic stress disorder, depression, substance use disorder, and general mental health were examined. This review began with a search for assessment tools in PubMed, PsycINFO, and Google Scholar. Next, validation studies for the tools were obtained through snowball sampling. A final search was conducted for scientific studies using the selected tools in humanitarian settings to collect the data for analysis. The benefits and limitations described for each tool were compiled into a complete table. Results Twelve assessment tools were included, with 88 studies using them. The primary findings indicate that half of the studies used the Impact of Events Scale-Revised. The most common limitation discussed is that self-report tools inaccurately estimate the prevalence of mental health problems. This inaccuracy is further exacerbated by a lack of cultural appropriateness of the tools, as many are developed for Western contexts. Conclusion It is recommended that researchers and humanitarian workers reflect on the effectiveness of the mental health assessment tool they use to accurately represent the populations under study in emergency settings. In addition, mental health assessment should be coupled with action.